Analisis Perangkat Pembelajaran Guru Pendidikan Jasmani Olahraga Dan Kesehatan SD Se Kota Kupang - Lukas M.Boleng; Veramyta M.M.Flora Babang; Michael J.H Louk (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2018)
Learning tools have important functions in the learning process, among others, the first learning device is seen as a guide, the learning tool is as a guide or direction for a teacher. This is important because the learning process is something that is systematic and patterned. There are still many teachers who are lost direction or confused in the middle of the learning process just because they do not have learning tools. Therefore, learning tools provide guidance on what a teacher should do in the classroom. In addition, learning tools provide guidance in developing teaching techniques and provide guidance for designing better devices; second, learning tools are viewed as benchmarks, a professional teacher will evaluate each of his teaching outcomes. There are so many benefits of the preparation of learning tools, but the reality of the field is still a lot of obstacles and obstacles from teachers to create and prepare learning tools properly and correctly, where learning tools that should have mastered teachers and teachers should be prepared before teaching and learning activities occur precisely less prepared good and in some cases the preparation of learning tools is not in accordance with the guidelines for the preparation of the supposedly whereas by making a learning tool with a good teacher to carry out the learning process more programmed, planned and professionalism as teachers can be improved. A teacher of Physical Education of Sport and Health should also be able to make planning in learning, one of which is the implementation plan of learning. Learning implementation plan is a learning tool created by a teacher in planning learning activities with several meetings or face to face. In addition, a physical education teacher sports and health should also be able to carry out learning in accordance with the implementation plan of learning Based on this, the researcher will examine the analysis of learning device of Physical Education Teacher of Sport and Elementary School School in Kupang city to identify learning device compiled and implemented by Physical Education teacher of Sport And Health in elementary school